Developing a student mental health policy for a South African university: Consultation, contestation and compromise - Kaminer, D.; Shabalala, N. (South African Journal of Higher Education, 2019)
Given high rates of student mental health difficulties globally, the need for universities to have a student mental health policy has been increasingly recognised. In the South African context, such policies must not only balance the mental health needs of students with the realistic constraints of university resources in a time of austerity, but also engage with complexities posed by the Global North foundations of the fields of psychology and psychiatry and the systemic determinants of mental health. This article describes the development of a student mental health policy at a South African university, with a focus on points of contestation that emerged out of a broad-based institutional consultation process. Areas of contestation included the scope of university support for student mental health, defining mental health difficulties, the use of a disability framework for mental health, and processes of verification. All of these were embedded within a broader tension between health and social justice discourses. The compromises that were designed to balance these complexities within the student mental health policy are discussed, and reflections are offered that may inform the development of student mental health policies at other South African universities.